Managing Conflict and Negotiation in the Workplace: A Systematic Review of Strategies, Employee Psychology, and Leadership - Heni Hernawati; Janah Sojanah (The Indonesian Institute of Science and Technology Research, 2026)
Conflict and negotiation are key dynamics in modern organizations that influence the quality of working relationships, the effectiveness of collaboration, and the sustainability of performance. This study aims to synthesize the latest empirical findings on the relationship between conflict and negotiation through a Systematic Literature Review (SLR) approach based on the PRISMA guidelines. A search of the Scopus database for publications from 2020 to 2025 yielded 1,030 initial articles, which were gradually selected until 10 core articles were selected that integrated conflict and negotiation in an organizational context. Descriptive and thematic analyses were conducted to answer three research questions: (RQ1) the influence of conflict and negotiation strategies on the effectiveness of conflict resolution; (RQ2) the role of emotional and psychological factors in shaping employee behavior; and (RQ3) the influence of social identity, organizational culture, and leadership support on conflict dynamics. The results of the study show three main findings: collaborative strategies are more effective than competitive strategies; psychological factors such as mindfulness and emotional intelligence significantly influence employee responses; and professional identity, organizational culture, and supervisor support play an important role in preventing conflict escalation and increasing the success of negotiations.